2021
DOI: 10.3389/fphys.2021.782760
|View full text |Cite
|
Sign up to set email alerts
|

Acute Heart Failure After Reperfused Ischemic Stroke: Association With Systemic and Cardiac Inflammatory Responses

Abstract: Patients with acute ischemic stroke (AIS) present an increased incidence of systemic inflammatory response syndrome and release of Troponin T coinciding with cardiac dysfunction. The nature of the cardiocirculatory alterations remains obscure as models to investigate systemic interferences of the brain-heart-axis following AIS are sparse. Thus, this study aims to investigate acute cardiocirculatory dysfunction and myocardial injury in mice after reperfused AIS. Ischemic stroke was induced in mice by transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Various clinical and experimental studies showed that sympathetic overdrive and reduced parasympathetic activity might be the key mediator between stroke and cardiac events including arrhythmia 25 . Besides, experimental studies showed that stroke-heart syndrome was accompanied by systemic inflammation and suggested that inflammation was involved in the pathogenesis of stroke-heart syndrome 26 . Similarly, autonomic dysfunction and inflammation were also important drivers of depression including post-stroke depression 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Various clinical and experimental studies showed that sympathetic overdrive and reduced parasympathetic activity might be the key mediator between stroke and cardiac events including arrhythmia 25 . Besides, experimental studies showed that stroke-heart syndrome was accompanied by systemic inflammation and suggested that inflammation was involved in the pathogenesis of stroke-heart syndrome 26 . Similarly, autonomic dysfunction and inflammation were also important drivers of depression including post-stroke depression 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments have demonstrated a fourfold increase in cTn level in mice 24 h after middle cerebral artery occlusion (MCAO), correlating with elevated mortality [72]. High initial and peak cTn levels are associated with poorer neurological outcomes and increased mortality, with dynamic cTn changes doubling in-hospital death risk [35].…”
Section: Cardiac Troponin Elevationmentioning
confidence: 99%
“…Inflammatory responses and immune regulation significantly impact stroke-cardiac interactions [72,84,85,95]. Ischemic stroke (IS) induces systemic and local cardiac inflammation and causes acute HF with increased circulating cTn levels and bradycardia [72,96,97]. Interleukin (IL)-1 is pivotal in SIHI by enhancing the inflammatory response [5].…”
Section: Immune Response and Inflammationmentioning
confidence: 99%
“…TMAO, a metabolite derived from gut microbes, also adversely affects cardiomyocytes and coronary endothelial cells ( Peh et al, 2022 ). An animal study illustrated that the number of granulocytes in myocardial tissue increased, and the concentrations of proinflammatory cytokines IL-1β and IL-6 were also nearly doubled in mice after transient middle cerebral artery occlusion (tMCAO), which could lead to cardiac dysfunction and hemodynamic impairment ( Vornholz et al, 2021 ). Hermanns et al found that in middle cerebral artery occlusion (MCAO) mice, the severity of neuroinflammation correlated with cardiac function.…”
Section: Inflammation In Brain-peripheral Crosstalk After Ischemic St...mentioning
confidence: 99%